1719e Intercountry networking occupational health services in japan and asia. (24th April 2018) - Yoshikawa, Toru; Kogi, Kazutaka
Abstract : The collaboration through inter-country networking in facilitating prevention-oriented programmes in occupational health services (OHS) is discussed. Experiences within our Asian regional networking of action-oriented approaches are examined to know types of support that can effectively facilitate the situation-based OHS including those for small-scale workplaces. Commonly effective collaborative actions through the networking of action-oriented programme within OHS are reviewed. The networking has evolved since the 1990s to mutually support these activities for small enterprises, trade unions and health care workers and stress prevention. Attention is paid to support measures effective for facilitating practical workplace-level improvements and toolkits development. The reviewed programmes have led to many work improvements in the different settings. The programmes apply locally tailored, action-oriented activities with the support of OHS teams. Prominent examples include Work Improvement in Small Enterprises (WISE) or similar methods for small workplaces, locally adjusted services and training in varied sectors and recent stress prevention interventions. The improvements achieved include many low-cost ones in work methods, physical environment and work organisation. Locally arranged networks of trainers are found instrumental in adjusting the methods to local situations. The collaborative actions of network partners are effective when they focus on the following aspects: universally applicable simple procedures translated into locally practicable low-cost improvements addressing multiple factors; participatory approaches building on local good practices; and use of participatory action-oriented toolkits comprising checklists and training guides. Inter-country collaboration in the form of joint development of action-oriented approaches and localised training toolkits has proven effective. Commonly useful support is to emphasise building on local good practices, focus on universally applicable improvement procedures and facilitation by means of locally adjusted toolkits for use by facilitators of immediate improvements. It is recommended to make full use of interactive regional networking incorporating these features.